Project assignments for statics - Fontane, Darrell, author; Balgopal, Meena, author; Atadero, Rebecca, author; Rambo-Hernandez, Karen, author (Colorado State University. Libraries, 2014)
The project assignments included in this document were used in addition to a traditional lecture based statics course in our research. However, these assignments can be adapted to fit a variety of course styles. We provide additional details of our course here to give an example implementation and context for some of the assignment requirements.

While projects appear to have much to offer engineering education, rigorous evaluations of the impact of projects on student outcomes are rare. The objective of the project is to study the incorporation of three group design projects into a sophomore level statics course and to measure the effect of the changes on student outcomes including content knowledge and various affective outcomes.
Research Initiation Grant: Problem/Project-Based Learning in Statics, a Stepping Stone to Engineering Education Research.
Keywords: communication; curriculum; evaluation tools; student design projects; engineering education; teamwork; evaluation findings